2005
DOI: 10.1097/01.ede.0000173043.85834.f3
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Polychlorinated Biphenyl Exposures in Relation to Fetal and Early Childhood Growth

Abstract: Maternally mediated exposure to PCBs may be detrimental to fetal growth, particularly in boys. These effects apparently are not persistent. Interpretation of greater childhood growth of girls is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
111
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 45 publications
9
111
7
Order By: Relevance
“…Hertz-Picciotto and colleagues [13] showed that in humans, in utero PCB exposure of males was associated with low birth weight and body weight for gestational age in boys, while in girls, in utero exposure was associated with shorter gestation. Within the same study, at five years of age, prenatal PCB exposure was associated with increased growth in girls but not boys [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hertz-Picciotto and colleagues [13] showed that in humans, in utero PCB exposure of males was associated with low birth weight and body weight for gestational age in boys, while in girls, in utero exposure was associated with shorter gestation. Within the same study, at five years of age, prenatal PCB exposure was associated with increased growth in girls but not boys [13].…”
Section: Discussionmentioning
confidence: 99%
“…The developmental origins of health and disease hypothesis, derived from the thrifty phenotype hypothesis put forth by Barker and Hales in 1992 [5], postulates that low birth weight offspring can result from insufficient nutrition in the intrauterine environment, leading to metabolic and other health derangements later in life [5][6][7][8][9][10]. In fact, maternal serum PCB levels in humans negatively correlate with infant birth weight and gestational age [11][12][13][14][15][16][17]. A meta-analysis comparing prenatal PCB exposure and birth weight effects across 12 European birth cohorts found a significant negative correlation between cord blood PCB levels and birth weight [11].…”
Section: Introductionmentioning
confidence: 99%
“…There were few results reported gender difference, they frequently indicated a stronger negative effect on the birth weight among male infants (Rylander et al, 1996;Baibergenova et al, 2003;Sonneborn et al, 2008;Hertz-Picciotto et al, 2005;Vartiainen et al, 1998). Previous reports have indicated that increased maternal serum PCBs levels are associated with reduced birth weight in male infants and have suggested a greater susceptibility of male conceptuses, either in the fetal or embryonic period (Sonneborn et al, 2008;Hertz-Picciotto et al, 2005). Some of the studies reporting gender difference in the PCBs effects did not actually measure PCBs levels, but used a surrogate for exposure such as estimated fish consumption (Rylander et al, 1996) or residential information (Baibergenova et al, 2003), which may entail greater errors in exposure classification.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of lower-level PCBs exposure during pregnancy observed associations with decreased birth weight and other growth parameters (Fein et al, 1984;Rylander et al, 1996: Rylander et al, 1998Patandin et al, 1998;Karmaus and Zhu, 2004;Hertz-Picciotto et al, 2005;Sagiv et al, 2007;Sonneborn et al, 2008). In the Lake Michigan fish consumer study, cord serum PCBs levels predicted LBW and smaller birth head circumference (Fein et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation